'Marcel, the dancing-master': A Note on the Closing Lines of An Introduction to the Principles of Morals and Legislation. Issue 1 (6th August 2013) - DE CHAMPS, EMMANUELLE
Abstract : In the 'Concluding note' to An Introduction to the Principles of Morals and Legislation ( IPML ), added in January 1789 to the original 1780 text, Bentham addresses highly theoretical questions in jurisprudence: 'What is a law? What are the different parts of a law?' He then demonstrates that only an imperative theory of legislation can provide adequate answers and provide the means to establish a precise nomenclature of legal phenomena. These broad questions sum up the work conducted in the manuscripts Of the Limits of the Penal Branch of Jurisprudence, which remained at that time unpublished. After such abstract matter, Bentham concludes on a much lighter note:Leaning on his elbow, in an attitude of profound and solemn meditation, ' What a multitude of things there are ', (exclaimed the dancing-master Marcel), ' in a minuet ?' – May we now add? – and in a law .